An influence of some factors on the logopedic rehabilitation of patients after laryngectomy with tracheoesophageal bypass and voice prosthesis - E. V. Kosova; T. A. Petrova (Опухоли головы и шеи)
Tracheoesophageal bypass with endoprosthesis is one of the most important approaches for surgical ways of voice restoration after laryngectomy. Within after-surgery rehabilitation logopedic techniques may be practiced successfully for the patients undergone laryngectomy with tracheoesophageal bypass and voice prosthesis.